(untitled) (Research, Society and Development, 2021)
Horticultural residues can be used for growing mushrooms and obtaining proteolytic enzymes. The objective of this research was to evaluate the potential of lignocellulosic residues as substrates for mycelial growth and production of proteases by Lentinus crinitus. The matrix culture was prepared on potato dextrose agar (BDA) supplemented with yeast extract (YE) 0.5% (w/v). Vertical mycelial growth (VMC) was carried out in test tubes containing the following lignocellulosic residues supplemented with rice bran (FA): sawdust, (SER), açaí seed (SA) and pineapple exocarps (CAB), cupuaçu (CC) and tucumã (CT). Mycelial vigor was classified by the subjective method of notes. Proteolytic activity was determined using 1% (w/v) azocasein solution. The enzymatic characterization was carried out in the extract obtained from the cultivation of L. crinitus in the mixture of residues that favored the development of highly densified mycelium and significant production of proteases. Significant VMC was determined in SER+FA (0.40 cm/day). In CC+FA, L. crinitus developed a strongly densified mycelium. Significant proteolytic activity was determined in CC+FA (6.71 U/mL) and CT+FA (6.44 U/mL) cultures. In the extract of the culture in CC+FA there was a predominance of aspartic proteases that demonstrated an optimal activity at pH 5, at 50 ° C. These enzymes were strongly inhibited by Zn+2 and Mn+2. Residues from Amazonian horticulture used favor the production of mycelial mass and proteases by L. crinitus.